STUDI ANOMALI MAGNETIK TOTAL UNTUK PENCARIAN DAERAH PROSPEK HIDROKARBON DAERAH PULAU BURU PROVINSI MALUKU (Jurnal Geomine, 2015)
Geomagnetic measurements have been done on the island of Buru, Maluku region to estimate subsurface models. After processing the data contained a path in which there is a points of measurement (station) with a certain spacing. At each point of measurement stations will be obtained susepbilitas different values - different at each point of the station. The existence of a source that causes a disturbance in the magnetic field, the disorder is called magnetic anomalies.The method used to model the subsurface using software Mag2DC to obtain all the possible sources of anomaly that exist below the surface. Both anomalies that are shallow (residual) and anomalies that are in the (regional). Interpretation of magnetic anomaly produce subsurface structure, as a result of the incision that region Buru eastern Maluku province there are rocks hydrocarbon carrier but has been interpreted that the surface structure of the region there is a trap structural hydrocarbon traps.